New Orleans : A Chronological & Documentary History, 1539-1970 - Compiled and Edited by Siegel, Martin; Series Editor Furer, Howard B. (Dobbs Ferry Oceana Publications, 1975)
A chronology of the development of New Orleans including pertinent documents and a bibliography.
Include Index and Bibliography
Keywords: Louisiana--New Orleans